Urban planning and the British New Right - Allmendinger, Philip, 1968-; Thomas, Huw, 1954- (Routledge, 1998)
Exposing the myth that has grown up around Thatcherism, leading experts from a wide range of land-use policy areas examine the changes that were brought about in planning and the environment during the 1980s and 1990s.